On the review of electronic technologies applied to implantable medical devices - Ronny García-Ramírez; Gabriel Madrigal-Boza; Edgar Solera-Bolaños; Muhammad Ali Siddiqi; Christos Strydis; Alfonso Chacón-Rodríguez; Renato Rimolo-Donadio (Tecnología en Marcha)
The development of electronic implantable medical devices (IMD) has been increasing over the years, targeting very diverse applications and implementing different technologies. The impact of IMDs in the treatment of different ailments like Parkinson’s disease, hearing impairment, heart arrhythmia, and chronic pain, among many others, has been notorious and inspired their exploration to treat other health problems. Even when there is great interest in the scientific community for the exploration and development of IMDs, no standards are ruling its development. This lack of standardization is the reason why the analysis of the tendencies of this area from the technical point of view becomes complex. The analysis of the tendencies in the development of IMD devices required the exploration of diverse sources, which describe heterogeneous systems using very different approaches and methodologies for similar problems. In this paper an open SQL database intended for collecting information from IMD publications is presented; at this point, more than 200 published works are feed in the database covering a period from 1974 to 2018. This database is extensible and enables researchers to find trends and explore the development of IMDs from a broader perspective. We also used this database as a proof of concept to explore some general trends in the design of  IMDs based on the included works.